Application of the Qualitative Method of Analyzing Multivoicedness to Psychotherapy Research: The Case of "Josh". Issue 2 (3rd April 2021) - Kay, Emma; Gillespie, Alex; Cooper, Mick
Abstract: The multivoicedness of the self has become an important theoretical concept that is influencing modern psychotherapy research, with consensus that individuals should be studied within their social contexts. However, there are few qualitative tools that can help to develop in-depth, "thick" understandings of this multivoicedness. The qualitative method for analyzing multivoicedness (QUAM) is an innovative, systematic research tool for analyzing internal I-positions, external I-positions, and their interactions. QUAM was developed within a social psychological context, and in this article we consider its applicability to the psychotherapy research field. Transcripts from the first, 12th, and 24th (final) therapy sessions in a single case study of a client with depression were analyzed using QUAM. Through this analysis, we found that QUAM permitted a close inspection of the individual in their social context, through an examination of the dialogs that were generated around a range of internal and external I-positions. The main strength of the method was being able to analyze the origins and changes in the relation between internal and external I-positions. The main limitation is in reliably distinguishing I-positions.